El envejecimiento de la población: un fenómeno que está cambiando radicalmente la sociedad - García-Valdecasas, José Ignacio (Razón y fe, 2019)
This article has a fivefold aim: first, to define social ageing and distinguish it from chronological, physical and mental ageing; second, to describe empirically the phenomenon of population ageing, especially in modern societies; third, to investigate the causes and social consequences of such ageing; fourth, to discuss the meaning of agony, death and mourning in modern societies; and, finally, to address the possible future scenarios that older people can expect.
Keywords: social ageing; active ageing; agony; death; mourning